Canopy cover evolution, diurnal patterns and leaf area index relationships in a Mchare and Cavendish banana cultivar under different soil moisture regimes - Stevens, B.; Diels, J.; Vanuytrecht, E.; Brown, A.; Bayo, S.; Rujweka, A.; Richard, E.; Ndakidemi, P.A.; Swennen, Rony L. (Elsevier, 2020)
The biggest abiotic threat to banana (Musa spp.) production is water deficit, but physiological indicators in plantations are lacking. Canopy Cover (CC) seems to be a relevant parameter, but so far not used in banana fields. Field experiments were conducted to determine the effect of optimal irrigation (FI) versus rainfed (RF) on CC and Leaf Area Indices (LAI) in two experiments with different cultivars (Mchare ‘Huti Green’ [HG, AA] and Cavendish ‘Grand Naine’[GN, AAA]) (n = 3 for HG, n = 4 for GN) until harvest of cycle 1 (C1), studying C1 and C2 plants. Soil moisture was followed using Time Domain reflectometry. CC and LAI were reduced 8–9 weeks after the start of soil moisture divergence between RF and FI treatments in both experiments (p < 0.05), leading to a reduction in CC growth rate (r) and maximum CC (CCmax) in RF plots (p < 0.05). On a daily timescale, CC varied diurnally (i.e. was reduced) under high evaporative demands, whereby soil moisture depletion increased the CC reduction. Cultivar specific CC-LAI curves were created following the Lambert-Beer equation, whereby HG had a lower extinction coefficient than GN (0.52 vs. 0.67). CC growth over time seems a promising indicator for water deficit in the field. Diurnally, CC is more affected by evaporative demand than soil moisture depletion, although soil moisture depletion increases CC diurnal drops under high ET0.